Various mechanisms of myocardial necrosis development due to combat injury as a reason for discussion: a case series - I. M. Lovkin; N. M. Sydorova; A. P. Kazmirchuk; L. L. Sydorova; K. I. Tabakar; M. I. Mandzii (Zaporožskij Medicinskij Žurnal)
The real clinical practice of the last 8 years in Ukraine indicates the possibility of myocardial injury developing in wounded with combat trauma, including those meeting the criteria for myocardial infarction (predominantly type 2), which differs significantly in the mechanism of development, resulting in numerous difficulties for doctors in providing medical care to such patients (formulation of the diagnosis, choice of treatment tactics). The current recommendations of the European Society of Cardiology for the management of patients with acute coronary syndromes after the adoption of the Fourth Universal Definition of Myocardial Infarction do not consider special approaches to the treatment of patients with myocardial necrosis associated with trauma.